Computational analysis of the influence of residual stress on the strength of composites with different aluminum matrices and carbide particles - Balokhonov, Ruslan R.; Zemlianov, Aleksandr; Gatiyatullina, Diana; Romanova, Varvara A. (Metals)
A numerical study of the mechanical behavior of aluminum matrix-carbide particle composites subjected to combined thermomechanical loading is carried out. The composite structure, corresponding to that observed experimentally, is explicitly taken into account in the calculations. The mechanical response of the aluminum matrix and carbide particles is described using the isotropic elastic-plastic and elastic-brittle models. A fracture criterion of the maximum equivalent stress acting in the local regions of volumetric tension is used to study the crack initiation and propagation in the particles. The dynamic plane stress boundary value problems of cooling and tension of the composites are solved by the finite element method ABAQUS/Explicit. The influence of the coolinginduced residual stress and thermomechanical properties of the matrix and particle materials on the strength of the composites is investigated. A positive or negative effect of the residual stress is found to depend on the ratio between the particle strength and the matrix yield stress. Compressive residual stress formed in the particle after the cooling increases the strength of composites with hard matrices and low-strength particles. A decrease in the matrix-particle interfacial curvature results in a change in the fracture mechanism from in-particle cracking to debonding, which increases the composite strength. Composite elongation upon the fracture onset decreases with the volume fraction of the particles.